Impact of the Warburg effect on nucleotide homeostasis in human retinal endothelial cells and its relevance to proliferative diabetic retinopathy - Gregory, Andrew; Awad, Ahmed M.; Eltanani, Shaimaa; Yumnamcha, Thangal; Hart, Jenna; Me, Rao; Lin, Xihui; Shawky, Mohamed; Ibrahim, Ahmed S. (Frontiers in Pharmacology, 2025)
PurposeWhile great progress has been made in screening methods and therapies for proliferative diabetic retinopathy (PDR), it is still a major cause of blindness. Rapidly dividing cells reprogram their metabolism toward hyperglycolysis (the Warburg effect), a process recently implicated in angiogenesis. In this study, we sought to investigate nucleotide metabolism in human retinal endothelial cells (HRECs) under high glucose (HG) and hypoxia (Hyp), both key risk factors in PDR and known to induce the Warburg effect, and to validate these findings in patients with PDR.MethodsHRECs were cultured under normal conditions and then exposed to HG, Hyp, or both. Metabolomic profiling was performed using liquid chromatography-mass spectrometry (LC-MS/MS) to quantify nucleotide-related metabolites. In parallel, proteomic analysis was conducted to assess proteins involved in nucleotide metabolism. To validate the in vitro findings, vitreous samples from patients with PDR and non-PDR controls were analyzed. Receiver operating characteristic (ROC) analysis was then applied to evaluate the diagnostic potential of nucleotide metabolites in PDR.ResultsHG and Hyp in HRECs caused selective disruptions in nucleotide metabolism, marked by significant accumulation of D-ribose-5-phosphate, a glycolytic precursor for both purines and pyrimidines, as well as nucleoside mono- and diphosphates (NMPs, NDPs), particularly adenosine mono- and diphosphates (AMP and ADP), without global changes in total nucleotide pools. This accumulation was also observed in vitreous samples from patients with PDR. ROC analysis identified AMP+ADP levels >0.0062 µM as a potential diagnostic biomarker for PDR with 87.5% specificity. Proteomic profiling revealed dysregulation of key enzymes regulating nucleotide homeostasis, including reduced expression of mitochondrial nucleoside diphosphate kinase (NME4), increased levels of cytosolic adenylate kinase (AK1), and upregulation of multiple enzymes involved in de novo and salvage nucleotide biosynthesis. Notably, expression of ribonucleotide reductase catalytic subunit M (RRM2), which converts NDPs to deoxynucleotides (dNDPs) for DNA synthesis, was also elevated.ConclusionExposure to HG and Hyp, key risk factors for PDR, disrupts nucleotide homeostasis in HRECs, with enhanced glycolytic flux fueling nucleotide precursor production and altered kinase expression favoring the accumulation of nucleoside mono- and diphosphates over triphosphates. The corresponding increase in AMP and ADP in PDR vitreous highlights their potential as biomarkers and underscores the central role of nucleotide metabolism in PDR pathogenesis.